Determinants of primary care physicians’ intention to provide breast cancer screening services for rural women: a structural equation model based on the theory of planned behavior - Zhao, Yinren; Zhang, Zixuan; He, Yubai; Gu, Zixin; Yang, Fan; Hu, Zhiqing; He, Yuan (Frontiers in Public Health, 2025)
BackgroundBreast cancer has been a serious health problem worldwide. Early detection is undoubtedly effective in combating severe public health problems in developing countries. Meanwhile, primary care physicians play an important role in implementing screening programs. The objective of our study was to evaluate the determinants of primary care physicians’ intention to provide the breast cancer screening services (BCSs) for rural women.MethodsWe conducted a cross-sectional survey in 24 towns in Jiangsu Province. A total of 1,101 primary care physicians participated in and completed the study. The data collection tool was developed based on the theory of planned behavior (TPB), which includes attitude, subjective norms, and perceived behavioral control, as well as extended components including knowledge of BCSs and past providing-BCSs behavior.ResultsThe results of our study showed that subjective norms (β = 0.352, p < 0.001) had the strongest influence on primary care physicians’ intention to engage in breast cancer screening, followed by attitudes and perceived behavioral control. Both screening knowledge and past screening provision behavior had an indirect effect on behavioral intentions.ConclusionThe present study demonstrated that extended TPB is an effective model for explaining primary care physicians’ intention to engage in breast cancer screening programs. Meanwhile, our findings provide a reference for governments, hospitals and policies aiming to increase primary care physicians’ intention to provide rural women with BCSs.